Effects of heat transfer based water for three square multilayer absorber solar collector - Mohd Amiruddin, Fikri; Fatin Fatihah, Asri; Wan Mohd Faizal, .; Hasyiya Karimah, Adli; R., Mamat; Azmi, W. H.; A. I., Ramadhan; Talal, Yusaf (IOP Publishing, 2020)
Solar energy is one of the best sources of renewable energy with minimal environmental impact. In this study, the effect of absorber solar collector on the performance of the solar water heating system has been experimentally investigated. This study is aimed to obtain the output of temperature for absorber solar collector based on water moving to the system. In the solar water heating system, volume flow rate with 2, 3 and 4 liters per minute for each solar radiation for 300, 500 and 700 W/m2 respectively. The result indicates at higher temperature output at 700 W/m2 of solar radiation within 30 minutes during charging and discharging process at volume flow rate 4 l/m is 36.9 °C. A little bit difference for 300 and 500 W/m2 which are 36 °C and 36.6 °C respectively. Solar water heating systems, in difference collectors have long distance, have temperature increases based on water medium in the system. Heat transfer performance with different radiation intensities of 300, 500 and 700 W/m2. The heat transfer performance for radiation of 700 W/m2 shows the highest followed by 500 W/m2. The lowest heat transfer performance is seen at 300 W/m2.